Can a professional development workshop with follow-up alter practitioner behaviour and outcomes for neck pain patients? A randomised controlled trial. (September 2016) - Chipchase, L.S.; Cavaleri, R.; Jull, G.
Abstract: Background: Continuing professional development (CPD) is a fundamental component of physiotherapy practice. Follow-up sessions provide opportunity for the refinement of skills developed during CPD workshops. However, it is necessary to identify if such opportunity translates to improved physiotherapist performance and patient outcomes. Objectives: To determine whether a traditional CPD workshop with a follow-up session with the educator is more likely to change physiotherapists' practice behaviour and patient outcomes than a traditional workshop with no opportunity for follow-up. Design: A single-blind, randomised controlled trial. Methods: Participants were stratified and randomly allocated to the intervention and control groups. The control group participated in a two-day workshop dedicated towards the management of neck disorders. The intervention group completed the two-day workshop and attended a five-hour follow-up session one month later. Outcome measures included self-reported physiotherapist practice behaviour and confidence, as well as patient clinical outcomes using the Neck Disability Index. Results: While all participants exhibited changes in confidence and practice behaviours, between-group differences were not significant for any response (p > 0.05). There were also no significant differences between the groups in terms of patient outcomes (Neck Disability Index: F = 0.36, p = 0.56). Conclusion: A single follow-up session to a traditional workshop is insufficient to significantly influence practice behaviours or patient outcomes. Highlights: A CPD workshop with follow-up resulted in no changes to physiotherapist practice or confidence when compared to a workshop with no opportunity for follow-up. No differences in patient outcomes were found with the addition of a follow-up session. Further research is needed to evaluate outcomes following CPD.